Constructivist Learning Paradigm as the Basis on Learning Model Development - Kurniawan Yudhi Nugroho (Journal of Education and Learning (EduLearn), 2017)
Research on the knowledge quality development has advanced very rapidly in these recent years. Yet, researchers have conducted their studies mostly in a specific issue within the frame of classroom teaching. This paper aims at presenting the conceptual design of academic knowledge development based on the theories of constructivist learning. These theories suggest that learning process should have been able to provide students with opportunities to get involved in an active process to make sense of new experience by connecting ideas with the basic knowledge they have. In addition, this conceptual design is made as an endeavor to discuss how the theories of constructivist learning may impact to the students’ knowledge quality enhancement. This paper would also discuss about how the concept of constructivist learning impacts to learners’ academic learning environment, learning participation and learning responsibility.